MODEL PENANGGULANGAN TINDAK PIDANA DENGAN MENGOPTIMALKAN FUNGSI BHAYANGKARA PEMBINA KEAMANAN DAN KETERTIBAN MASYARAKAT DI WILAYAH HUKUM KEPOLISIAN RESOR KABUPATEN KAMPAR - Fuad Ikmal; Davit Rahmadan; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Crime prevention is one of the primary roles of the Police in maintaining thesecurity and order of society. In carrying out their duties, the Indonesian NationalPolice (Polri) has a unit called Bhayangkara Pembina Keamanan dan KetertibanMasyarakat (Bhabinkamtibmas), which serves as the frontline in establishingrelationships with the community at the village or sub-district level. However, inthe jurisdiction of the Kampar District Police Resort, there are still several issuesthat hinder the optimization of Bhabinkamtibmas' functions.This research aims to analyze a model for combating crime by optimizingthe functions of Bhabinkamtibmas in the jurisdiction of the Kampar DistrictPolice Resort. The background of this research is based on the need to improveand enhance the effectiveness of Bhabinkamtibmas in preventing and handlingcriminal acts at the community level. The research utilizes a qualitativedescriptive method with a case study approach. Data is obtained throughinterviews with several Bhabinkamtibmas officers in the area and from relevantliterature studies.The research employs a qualitative approach with data collectiontechniques such as interviews, observations, and documentary studies. Therespondents consist of Bhabinkamtibmas officers, local communities, and otherrelevant stakeholders.The results of the research indicate that Bhabinkamtibmas plays a crucialrole in maintaining the security and order of society in the jurisdiction of theKampar District Police Resort. Bhabinkamtibmas can undertake variouspreventive actions to deter criminal activities, such as conducting routine patrolsin their respective areas, building good relationships with the community, andproviding education and information about laws and regulations. Additionally,Bhabinkamtibmas can take repressive measures against criminals bycollaborating with other security forces.Keywords: crime prevention model, Bhabinkamtibmas, communitysecurity and the Kampar District.